2012
DOI: 10.5012/bkcs.2012.33.6.1845
|View full text |Cite
|
Sign up to set email alerts
|

Layered Metal Hydroxides Containing Calcium and Their Structural Analysis

Abstract: Layered metal hydroxides (LMHs) containing calcium were synthesized by coprecipitation in solution having two different trivalent metal ions, iron and aluminum. Two mixed metal solutions (Ca 2+ /Al3+ and Ca 2+/Fe 3+ = 2/1) were added to sodium hydroxide solution and the final pH was adjusted to ~11.5 and ~13 for CaAl-and CaFe-LMHs. Powder X-ray diffraction (XRD) for the two LMH samples showed well developed (00l) diffractions indicating 2-dimensional crystal structure of the synthesized LMHs. Rietveld refineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…Figure 1 shows the X-ray diffraction patterns for the CaM-LDHs and their taurine intercalates. The diffraction patterns for the pristine LDHs corresponded well with previously reported results (Figure 1) [21,26]. After intercalation, the (00l) peaks shift to the lower 2-theta region, revealing lattice expansion from ∼8.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 1 shows the X-ray diffraction patterns for the CaM-LDHs and their taurine intercalates. The diffraction patterns for the pristine LDHs corresponded well with previously reported results (Figure 1) [21,26]. After intercalation, the (00l) peaks shift to the lower 2-theta region, revealing lattice expansion from ∼8.…”
Section: Resultssupporting
confidence: 89%
“…In a previous study [26], we reported that the bond distance between calcium and the seventh coordinated nitrate is approximately 2.3Å. The molecular dimensions along the z-axis for taurine (distance from outermost sulfate oxygen to amine hydrogen) and water are approximately 4.6 and 0.6Å, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…LDH consisted of calcium and aluminum (CaAl-LDH) was prepared through coprecipitation method, as previously reported [ 38 ]. Typically, NaOH solution (1.26 M) was added dropwise to the mixed metal chloride solution (0.315 M and 0.1575 M for CaCl 2 ·2H 2 O and AlCl 3 ·6H 2 O, respectively) until the pH reached to around 11.5.…”
Section: Methodsmentioning
confidence: 99%
“…These octahedra are connected to each other by edge sharing to form an infinite sheet. When the divalent ion is Ca(II), the structure is somewhat different; it is the hydrocalumite type structure (Evans & Slade, 2006;Taylor, 1969;Rousselot et al, 2002;Vieille et al, 2004;Kim et al, 2012). Its parent structure is that of portlandite.…”
Section: Introductionmentioning
confidence: 99%